2015
DOI: 10.1002/pon.3747
|View full text |Cite
|
Sign up to set email alerts
|

Managing fatigue after cancer treatment: development of RESTORE, a web‐based resource to support self‐management

Abstract: Objective: The aim of this study is to co-create an evidence-based and theoretically informed web-based intervention (RESTORE) designed to enhance self-efficacy to live with cancer-related fatigue (CRF) following primary cancer treatment.Methods: A nine-step process informed the development of the intervention: (1) review of empirical literature; (2) review of existing patient resources; (3) establish theoretical framework; (4) establish design team with expertise in web-based interventions, CRF and people aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 34 publications
0
30
0
Order By: Relevance
“…This in turn influences the perception of fatigue [26,28]. The intervention had five sessions, where sessions 1 and 2 included an introduction to fatigue and goal setting.…”
Section: Interventions To Support Self-managementmentioning
confidence: 99%
See 1 more Smart Citation
“…This in turn influences the perception of fatigue [26,28]. The intervention had five sessions, where sessions 1 and 2 included an introduction to fatigue and goal setting.…”
Section: Interventions To Support Self-managementmentioning
confidence: 99%
“…Sessions 3e5 were designed to cover areas of life where fatigue might have an effect and could be tailored to user preference. These life domains include home, work and emotional adjustment [28].…”
Section: Interventions To Support Self-managementmentioning
confidence: 99%
“…Usability in eHealth interventions is associated with both usage and effectiveness, 38,39 and usability studies have been used to develop and refine eHealth and mHealth interventions targeting a range of health behaviours, including the self-management of symptoms following treatment for cancer. 32,40 There is a range of methods available to test the usability of digital healthcare interventions including interviews with users, think-aloud methods and participant observation. 36,41 Peer review and publication of research protocols has been identified as an important early stage step in reducing publication bias and improving the quality of research.…”
Section: Introductionmentioning
confidence: 99%
“…Current evidence supports the use of nonpharmacological treatment strategies for reducing CrF [3]. Web-based interventions have been shown to be an effective mode of delivery and can facilitate self-management of long-term conditions [4,5], including CrF [6-9]. Chou, Liu, Post, and Hesse [10] encourage using the Internet to better serve survivors’ needs as it is increasingly being used as a resource by cancer survivors.…”
Section: Introductionmentioning
confidence: 99%
“…Such interventions may, therefore, increase access for users by providing 24-hour access to health care interventions and having the potential to reach huge numbers of people [11]. Use of such tools may enhance empowerment and effective self-management of fatigue [6,8]. …”
Section: Introductionmentioning
confidence: 99%